A plant economics spectrum of litter decomposition among coexisting fern species in a sub-tropical forest. (21st October 2019) - Lin, Dunmei; Yang, Shufang; Dou, Pengpeng; Wang, Hongjuan; Wang, Fang; Qian, Shenhua; Yang, Guangrong; Zhao, Liang; Yang, Yongchuan; Fanin, Nicolas
Abstract: Background and Aims: The plant economics spectrum theory provides a useful framework to examine plant strategies by integrating the co-ordination of plant functional traits along a resource acquisition–conservation trade-off axis. Empirical evidence for this theory has been widely observed for seed plants (Spermatophyta). However, whether this theory can be applied to ferns (Pteridophyta), a ubiquitous and ancient group of vascular plants, has rarely been evaluated so far. Methods: We measured 11 pairs of plant functional traits on leaves and fine roots (diameter <2 mm) on 12 coexisting fern species in a sub-tropical forest. Litterbags of leaves and roots were placed in situ and exposed for 586 d to measure decomposition rates. The variation of traits across species and the co-ordination among traits within and between plant organs were analysed. Finally, the influence of the traits on decomposition rates were explored. Key Results: Most leaf and root traits displayed high cross-species variation, and were aligned along a major resource acquisition–conservation trade-off axis. Many fern traits co-varied between leaves and fine roots, suggesting co-ordinated responses between above- and below-ground organs. Decomposition rates of leaves were significantly higher than those of fine roots, but they were significantly and positively correlated. Finally, our results highlight that the decomposition of both leaves and roots was relatively well predicted by the leaf and root economics spectra. Conclusions: Our results support the existence of an acquisition–conservation trade-off axis within ferns and indicate that traits have important 'afterlife' effects on fern litter decomposition. We conclude that the plant economics spectrum theory that is commonly observed across seed plants can be applied to ferns species, thereby extending the generality of this theory to this ancient plant lineage in our study site. Our study further suggests that the evolutionary and ecological basis for the relationships among key economics traits appears to be similar between ferns and seed plants. Future studies involving larger data sets will be required to confirm these findings across different biomes at larger spatial scales.